PEMAHAMAN PERAWAT DALAM PELAKSANAAN TRIAGE KECELAKAAN LALU LINTAS DI IGD - Muhammad Riduansyah; R. Topan Aditya Rahman; Raudana Saputra (CNJ: Caring Nursing Journal, 2021)
Triage is a process of selecting patients according to the level of emergency and priority in handling patients. Determination of priority treatment will be influenced by the level of emergency patients, the number of patients who come in, the ability of the emergency room staff, availability of supporting equipment and space. This study aims to determine the description of nurses' understanding in the implementation of Traffic accident Triage in the Emergency Room at Ulin Hospital Banjarmasin. Type of research is quantitative with descriptive research design. The sample in this study amounted to 30 nurses working in the ED selected by the Accidental Sampling technique using the Nurse Understanding Questionnaire and observation sheets. Based on the research results, the average level of understanding of nurses about Triage 26 (86.7%) is good, 4 (13.3%) is sufficient and while related to the implementation of Triage 27 (90%) is good, 3 (10%) is sufficient to be the implementation Triage in ED is good. The description of the understanding of the ED Ulin Banjarmasin Hospital nurses about Triage is included in the good category with good Triage implementation